PROFIL KEMAMPUAN KONEKSI MATEMATIS SISWA SMP DALAM MENYELESAIKAN SOAL PERSAMAAN GARIS LURUS - Dinda Risdayani; Alpha Galih Adirakasiwi (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2022)
Mathematical connection is one of the mathematical ability that need to be possessed and developed in students. Mathematical connection ability will help students build a much better understanding of mathematics. This research is a qualitative descriptive study that aims to describe students' mathematical connection ability in solving straight line equations. The research subjects in this study were three students of class VIII-D at SMPIT Nurul Husna Bekasi Regency, from 14 people. Subject selection based on written test results. The data collection technique described the mathematical connection ability test questions and interviews. Then, the data analysis technique used was data reduction, data presentation, and conclusion drawing. The study results showed that students with high mathematical connection ability had met the three indicators of mathematical connection, in contrast to students with low and medium ability who had not completed the three indicators of mathematical connections.